186 To tweet or not to tweet: what does science communication look like in 2019?. (5th December 2019) - Place, Sara E
Abstract: We live in an era of increasing data availability, from technology that allows for precise and repeated measures of animal behavior and physiology outcomes to the constant posts on Facebook from that uncle we see once per year at Thanksgiving. While it may seem disingenuous to compare data collected in a controlled experiment to social media posts, which has a larger impact on society? If research results that are relevant to public square debates about food and agriculture, such as animal welfare and environmental sustainability, are only published in academic journals and read and understood by peers, how will they inform the public debate? If animal scientists are not actively engaged in sustained communication (two-way dialogue, not one-way lecturing) than an uncle's Facebook post on factory farming may have a larger effect on the public debate than a carefully planned and executed experiment. In addition to data overload, we also seemingly have ever less time to process this data into meaningful and actionable information. As scientists, we are trained to interpret data into meaningful information. That skill is evermore needed and valuable to the public now. While engagement will look different depending upon each scientist's discipline, skills, and willingness to engage, we should not expect it is someone else's job to communicate the importance of animal science.